Psychosomatic aspects of the clinical picture and therapy of chronic pelvic pain in sexological practice - M. I. Yagubov; I. Yu. Kan (Лечащий Врач, 2021)
The article analyzes the results of a survey of 75 men who addressed to the department of sexology and therapy of sexual dysfunctions with pains in the pelvic region with which patients associated sexual disorders. In the course of the study, the authors studied the clinical aspects of these disorders, taking into account the diagnostic complexity of the qualification of similarity and the difference of the existing symptoms from the manifestations of a physical illness. The principles and tactics of therapeutic and rehabilitation measures, developed taking into account the structure of mental and sexual pathology, are presented.